Analysis of Added Value and Profitability of Ginger Chip Processing Business in Ulusena Village, South Konawe Regency - Zulyarson, La Ode Muhammad; Abdi; Zani, Munirwan (International Journal of Technology and Education Research, 2026)
This study aims to 1) analyze the added value generated from ginger chips processing in Ulusena Village, Moramo District, South Konawe Regency, and 2) analyze the profitability generated from ginger chips processing in Ulusena Village, Moramo District, South Konawe Regency. The research was conducted in Ulusena Village, Moramo District, South Konawe Regency from October to November 2024. The subjects of this study were the Women's Farmers Group (KWT) who are both the owners of the business and the processors of ginger chips products in Ulusena Village, Moramo District, South Konawe Regency. The added value of ginger chips processing was analyzed using the Hayami method, and the profitability of ginger chips processing was analyzed using the profitability analysis. The results of the study show that: 1) The difference between revenue and total production cost results in a net profit of IDR 1.288.959 per month. This profit reflects the profitability of the Harapan Jaya ginger chips processing business after deducting all production costs from the total revenue generated, indicating that the business has good financial performance, and 2) The added value generated from ginger chips processing is IDR 1,000 per kg with an added value ratio of 1.26%. This shows that although there is an increase in value from raw material to finished product, the increase is not very significant